Potential flight range of Snow Buntings Plectrophenax nivalis occurring in the Azores in late March : a first analysis. - Bolton, Mark (2001)
It has been known for many decades that Snow Buntings occur with some regularity in the Azores archipelago in winter, with flocks numbering up to 20 individuals on occasion. The majority of records are from the islands of Corvo and Faial. The origin and fate of these individuals is unknown and it is unclear whether the regular occurrence of such groups represents a wintering strategy, or rather, whether these birds have been blown off the course of their usual migration route. Seven individuals from a flock of ten Snow Buntings known to have been present on the island of Faial between 20th March and early May 2000 were trapped on March 30th 2000. Plumage characteristics indicated they were of the Greenland P.n. nivalis race. Measurements of body mass indicated that the fat reserves of these individuals were similar to those of Snow Buntings wintering in Scotland U.K. at the same time of year, just prior to departure to the breeding grounds. However the calculated potential flight range of the individuals from Faial varied from 500 km to 1.800 km, averaging 1.150 km for females and 1.640 km for males. Whilst these average ranges would be sufficient to make continental landfall if the birds followed an easterly route, such a heading is considered improbable, given their racial characteristics. The calculated energy reserves would be insufficient to sustain continuous flight on a northerly course to continental landfall. The presence of potentially suitable breeding habitat on the neighbouring island of Pico is highlighted.